Case report: Successful treatment of a patient undergoing haemodialysis with multifocal hepatocellular carcinoma using atezolizumab and bevacizumab - Abraham, Shalin; Samson, Adel (Frontiers in Oncology, 2024)
In the last five years, the advent of combination immune checkpoint inhibitor atezolizumab and anti-angiogenic agent bevacizumab has transformed treatment of unresectable hepatocellular carcinoma. As patient outcomes improve, healthcare professionals will more frequently encounter patients with concomitant hepatocellular cancer and end stage kidney disease on haemodialysis. We present the first case in the literature of a 58-year-old male with multifocal hepatocellular carcinoma undertaking regular haemodialysis who was successfully treated with atezolizumab and bevacizumab with a partial response and stable disease for two years, who suffered grade 1 fatigue, grade 2 hypertension and eventually grade 3 wound infection leading to cessation of bevacizumab. After disease progression on atezolizumab monotherapy, all chemotherapy was stopped. We embed this case in a review of the current literature of atezolizumab and bevacizumab use in patients undertaking haemodialysis and conclude that both targeted therapies may be safely used in these patients. We recommend joint close management of these patients between oncology and nephrology teams, with initial cardiovascular risk stratification before commencing atezolizumab and bevacizumab therapy. During therapy, there should be regular monitoring of blood pressure, or proteinuria if the patient is oliguric under guidance of the dialysis team if preservation of residual renal function is required.